[PP.27.25] DIAGNOSTIC VALUE AND REFERENCE INTERVALS OF PLASMA FREE METANEPHRINES MEASURED BY LC-MS IN A POPULATION REFERRED TO A HYPERTENSION EXCELLENCE CENTER. (September 2017) - Barigou, M.; Billaud, E.; Putrus, R.; Baron, S.; Bobrie, G.; Blanchard, A.; Gimenez-Roqueplo, Ap; Azizi, M.; Amar, L.
Abstract : Objective: -To determine reference intervals of plasma metanephrines(pl-MTN) and normetanephrines(pl-NMT) measured by Liquid chromatography with mass-spectrometry(LC-MS), in semi-recumbent standardized position in hypertensive population referred to an excellence center. -To evaluate the sensitivity/specificity of pl-MTN/pl-NMT in semi-recumbent position compared to seated position, and 24 h urinary metanephrines (24hUr-MTN) for the diagnosis of secreting pheochromoctyoma/paraganglioma(PPGL). -To evaluate the correlation between plasma and urinary MTN/NMTby LC-MS method. Figure. No caption available. Design and method: We conducted a retrospective overview of electronic registers of the Hypetension Unit of Georges Pompidou European hospital, from May 2014 to May 2016 to identify patients who completed a PPGL workup: -concomitant determination of plasma and urinary MTN/NMT by LCMS, -Imaging examinations to confirm/exclude PPGL. -The diagnosis of PPGL was made after surgery by histopathology. All patients under medications interacting with MTN/NMT secretion were excluded. 250 patients corresponded to the inclusion criteria, 169 had a pl-MTN/NMT determination after 30 minutes of semi-recumbent standardized position (145 negative/24 positive for PPGL), and 81 were sampled in seated position (69 negative/12 positive for PPGL)(fig1). Reference intervals were established from the (2.5th-97.5th)percentiles in patients without PPGL. Results: -Reference intervals in standardized semi recumbent position were estimated at [0.1–0.47nmol/l] for pl-MTN and [0.23–1.10nmol/l] for pl-NMT -Compared to the seated group, the semi-recumbent group showed a significantly lower mean value of pl-NMT (0.59 ± 0.23 Vs 0.72 ± 0.34nmol/l p = 0.006), with a lower 'upper reference interval value'(URV)[1.10 Vs 1.5nmol/l] -ROC analysis of pl-NMT for the diagnosis of PPGL showed an increased AUC (0.995 Vs 0.958), a higher sensitivity (95.8% Vs 91.6%) and specificity (97.2% Vs 97.1%) at the URV (97.5th percentile)in the semi-recumbent group Vs seated group. -Comparison of ROC paremeters of pl-NMT in semi-recumbent position, 24hUr-NMT and 24hUrNMT/creatininuria at optimal criterions for the diagnosis of PPGL showed the highest combination of sensitivity/specificity for pl-NMT (95.8%/97.2%) vs (94.4%/95.7%) for 24hUr-NMT and (91.6%/96.7%) for 24hUrNMT/Creatininuria. -Pl-NMT correlated to 24hUr-NMT with a correlation coefficient r = 0.971 (p < 0.0001) Conclusions: pl-NMT measured by LC-MS in semi-recumbent position offered high sensitivity/specificity values for the diagnosis of PPGL. Reference intervals described in our study are comparable to those previously reported in the literature. pl-MTN/NMT correlated well to Ur-MTN/NMT.